The effect of deep cryogenic treatment on SnSb/C nanofibers anodes for Li-ion battery. (20th December 2016) - Xia, Xin; Li, Zhiyong; Zhou, Huimin; Qiu, Yiping; Zhang, Chuyang
Abstract: In order to improve the cycling stability of SnSb/C nanofiber anodes for Li-ion batteries, the deep cryogenic treatment was firstly used to modify the morphology structure of SnSb/C nanofibers. Three different processing schedules were employed to treat SnSb/C precursor nanofibers including direct carbonization, deep cryogenic treatment & carbonization, and carbonization & deep cryogenic treatment. The morphology structure, especially the morphology rebuilding mechanism has been evaluated after being treated by these three schedules. The decreased-porous and increased-porous SnSb/C nanofibers were rebuilt because the increased carbon trapped in pores to close some pores and induced more CO2 evolution to create more pores, respectively. The SnSb/C nanofiber anodes with more pores and larger surface area exhibited improved cycling stability and coulombic efficiency. The deep cryogenic treatment was successfully used to modify the morphologies and properties of nanofibers, it provided a new way to improve the electrochemical performance of nanofiber anodes.